Carrying Capacity Assessment Based on Chlorophyll-ain the Tajwid Lake, Langgam Sub-District, Pelalawan District, Riau Province for Extensive Fishing - Fadilah, Nisa Wangi Tresna; Simarmata, Asmika H.; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Carrying capacity is defined as the ability of aquatic environment to support the life organism in that area. A study aimed to assess the aquatic carrying capacity based on chlorophyll-a for extensive fishing was conducted in the Tajwid Lake. The carrying capacity was determined based on primary productivity (chlorophyll-a content), which is indicating the existence of phytoplankton in the water. This research was conducted in March-April 2018 in the Tajwid Lake. There were 3 stations, namely Station 1 (inlet area), Station 2 (in the middle of lake) and Station 3 (outlet area). Water quality parameters measured were temperature, transparency, pH, dissolved oxygen, CO2, nitrate, phosphate, and chlorophyll-a concentration. The concentration of chlorophyll-a indicates that the carrying capacity of the Tajwid lake for extensive fishing was 6.925 tons/year. Water quality parameters were as follows: transparency 47.0-54.7 cm, temperature 29.3-30.7oC, pH 5, dissolved oxygen 4.75-6.29 mg/L, CO2 17.32-22.64 mg/L, nitrate 0.0541-0.0820 mg/L, phosphate 0.1327-0.2798 mg/L, and concentration of chlorophyll-a was 7.96 µg/L.